Isoflurane-Induced Burst Suppression Is a Thalamus-Modulated, Focal-Onset Rhythm With Persistent Local Asynchrony and Variable Propagation Patterns in Rats - Ming, Qianwen; Liou, Jyun-You; Yang, Fan; Li, Jing; Chu, Chaojia; Zhou, Qingchen; Wu, Dan; Xu, Shujia; Luo, Peijuan; Liang, Jianmin; Li, Dan; Pryor, Kane O.; et al. (Frontiers in Systems Neuroscience, 2021)
BACKGROUND: Inhalational anesthetic-induced burst suppression (BS) is classically considered a bilaterally synchronous rhythm. However, local asynchrony has been predicted in theoretical studies and reported in patients with pre-existing focal pathology. METHOD: We used high-speed widefield calcium imaging to study the spatiotemporal dynamics of isoflurane-induced BS in rats. RESULTS: We found that isoflurane-induced BS is not a globally synchronous rhythm. In the neocortex, neural activity first emerged in a spatially shifting, variably localized focus. Subsequent propagation across the whole cortex was rapid, typically within 100 milliseconds, giving the superficial resemblance to global synchrony. Neural activity remained locally asynchronous during the bursts, forming complex recurrent propagating waves. Despite propagation variability, spatial sequences of burst propagation were largely preserved between the hemispheres, and neural activity was highly correlated between the homotopic areas. The critical role of the thalamus in cortical burst initiation was demonstrated by using unilateral thalamic tetrodotoxin injection. CONCLUSIONS: The classical impression that anesthetics-induced BS is a state of global brain synchrony is inaccurate. Bursts are a series of shifting local cortical events facilitated by thalamic projection that unfold as rapid, bilaterally asynchronous propagating waves.